Poole's Casebook on Contract Law - Robert Merkin QC; Severine Saintier (United Kingdom Oxford University Press, 2021)
All the cases you need, together with the tools to understand them.This contract casebook presents all the leading cases, supplemented by succinct author commentary and thought-provoking questions to deepen your understanding. Poole's Casebook on Contract Law takes a uniquely supportive approach to give students the confidence to engage with and analyse judgments.
Keywords: Contract law; Law; (ASB-2400) Law for Business